Development of a Survey to Assess Latino Fathers' Parenting Practices Regarding Energy Balance–Related Behaviors of Early Adolescents. (February 2020) - Zhang, Youjie; Reyes Peralta, Alejandro; Arellano Roldan Brazys, Patricia; Hurtado, Ghaffar Ali; Larson, Nicole; Reicks, Marla
Latino adolescents face challenges to performing energy balance–related behaviors (EBRBs) to prevent childhood obesity, including healthy dietary intake, adequate physical activity, and limited screen time. Fathers are underrepresented in family-based obesity interventions but could be influential in shaping the EBRBs of Latino children. Three types of parenting practices (setting expectations/limits, role modeling, managing availability and accessibility) have shown relatively consistent positive relationships with children's EBRBs in studies that have mostly involved mothers. The purpose of this study was to develop measures to assess Latino fathers' parenting practices based on existing measurement instruments, focus groups and cognitive testing. Criterion validity of the measures (40 items) was examined with Latino fathers and their early adolescents (10-14 years old, n = 96 dyads) who were predominantly from low-income, two-parent households. Criterion validity was indicated by significantly higher intakes of fruit and vegetables; lower intakes of sugar-sweetened beverages, sweets/salty snacks and fast foods; more weekly physical activity hours; and fewer daily screen time hours among adolescents who reported high versus low levels/frequencies of supportive parenting practices. In addition, nearly all scales of adolescent-reported paternal behavioral modeling and availability/accessibility practices were significantly correlated with adolescents' corresponding EBRBs (r = 0.22 to 0.54). However, poor validity and agreement with early adolescents' reports were found for most father-reported parenting practices. Overall, this study indicated that the measures were acceptable for assessing adolescents' report of Latino fathers' parenting practices around EBRBs. The findings also indicate the importance of including early adolescents' reports in measuring paternal parenting practices.